Dialects, Beliefs and Practices of the Tinguians of Abra - Abaya, Digna Jocelyn; De Vera, Marciana; Bajet, Manuel (JPAIR Multidisciplinary Research, 2011)
This descriptive research identified the dialects,beliefs and practices of the Tinguians in Abra utilizing a questionnaire - checklist coupled with personal interview and ethnography. Of the twentyseven (27) municipalities of Abra, onlytwenty-two (22) speak the eleven (11) Ethno linguistic dialects: Adasen, Balatok, Banao, Belwang, Binongan, Gobang,Inlaud, Mabaka, Maeng, Masadiit and Moyadan; while Fourteen(14)municipalities speak the Inlaud dialect. Courtship was never practiced. Tani was the mode of marriage. The Danon was done on moonlight nights. The Sab-ong was discussed when the marriage was set. One is assigned for the Billite to all the relatives and friends when the marriage was set. The deads were not embalmed, thus, bagungon lasted only for three days. Somebody does the Beccaang to the relatives and friends about the death of a relative. Taradyo was collected. Tadek was danced during marriage and burial. Uggayamand Salidummay were chanted during death and danon. The deads were buried in the yards, under the houses orstairs. Balliwes was danced after the burial. Golgol was done a day after the burial. Today, Bagungon, Taradyo,Waksi and Tadek are still practiced. Tani, Danunand Sab-ong are no longer practiced. Billite and Beccaang are now obsolete ways of information during marriages and death of their relatives. Deads are already buried in cemeteries.
Keywords: Tinguians; Ethno-Linguistic Dialects; Cultural Practices; Traditional Beliefs; Abra; Philippines